2D magnetotelluric image of the Dobrá Voda seismoactive area - ONDRÁŠOVÁ, Lenka; VOZÁR, Ján; HÓK, Jozef; CIPCIAR, Andrej; GODOVÁ, Dominika; KLANICA, Radek (Contributions to Geophysics and Geodesy, 2022)
Dobrá Voda village is located in the Malé Karpaty Mts. (Brezovské Karpaty) and is well known for its increased seismic activity. For a better understanding of the processes preceding earthquakes, this area has been studied using several methods. One of them is magnetotellurics. Magnetotellurics provides an image of the distribution of electrical conductivity within the Earth and helps to determine individual tectonic structures, specifically faults. The shallow conductive structures are associated with Neogene sediments of the Danube Basin, sedimentary fill of the Dobrá Voda Depression, and partial nappes of Hronicum, probably saturated with water. Less conductive structures are the Fatricum sediments and the lowest conductivity values belong to crystalline basement of the Tatricum tectonic unit. Whole structure of the Dobrá Voda seismoactive area along our magnetotelluric profile is disrupted by NE–SW oriented normal faults. Based on the location of earthquake hypocentres, we can identify main seismoactive areas as crystalline complexes of Tatricum.